The Political Shift in Legal Power of the Judiciary Post Constitutional Amendment - Prasetyo, Dossy Iskandar (Unissula, 2024)
The purpose of this study examines the legal politics of the shift in judicial power after the constitutional amendment in Indonesia. This study was conducted using doctrinal legal research with a fundamental research approach, designed to gain a deeper understanding of law as a social phenomenon. The results of the study found that historically, the earliest shift in judicial power was related to the theory of shifting separation of powers and the imperative rule of law. The post-constitutional shift resulted from the amendment to the 1945 Constitution which expressly stated that the judiciary is independent. Judicial power is an independent power to organize justice in order to uphold the law and equality and judicial power is not only carried out by the Supreme Court, but also by the Constitutional Court, that the supreme court judge must have integrity and an impeccable personality, fair, professional, and experienced in the field of law, To guarantee the independence and integrity of judges, especially the amendment to the 1945 Constitution, a new institution was issued called the Indonesian Judicial Commission.